The discovery of eight z ~ 6 quasars from Pan-STARRS1. Issue Volume 9:Issue S304(2013) (25th July 2014) - Bañados, E.; Venemans, B. P.; Morganson, E.; Decarli, R.; Walter, F.; Chambers, K. C.; Rix, H-W.; Farina, E. P.; Fan, X.; Jiang, L.; McGreer, I.; De Rosa, G.; et al.
Abstract: High-redshift quasars are unique probes of the evolution of supermassive black holes and the intergalactic medium at the end of the epoch of reionization. We present the optical spectra of eight new z ~ 6 quasars selected from the Panoramic Survey Telescope & Rapid Response System 1 (Pan-STARRS1). Details of the selection strategy can be found in Bañados et al . (2014). With this work we increase the number of known quasars at z < 5.7 by more than 10%. The quasars discovered here span a large range of luminosities (19.6 ≤ z P1 ≤ 21.2) and are remarkably heterogeneous in their spectral features: half of them show bright emission lines whereas the other half show weak or no Lyα emission line. We find a larger fraction of weak–line emission quasars than in lower redshift studies, although still based on low number statistics, this may imply that the quasar population could be more diverse than previously thought.